2016
DOI: 10.1038/ncomms11032
|View full text |Cite
|
Sign up to set email alerts
|

Roquin recognizes a non-canonical hexaloop structure in the 3′-UTR of Ox40

Abstract: The RNA-binding protein Roquin is required to prevent autoimmunity. Roquin controls T-helper cell activation and differentiation by limiting the induced expression of costimulatory receptors such as tumor necrosis factor receptor superfamily 4 (Tnfrs4 or Ox40). A constitutive decay element (CDE) with a characteristic triloop hairpin was previously shown to be recognized by Roquin. Here we use SELEX assays to identify a novel U-rich hexaloop motif, representing an alternative decay element (ADE). Crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 41 publications
6
86
0
Order By: Relevance
“…7a) 30,31 . RC3H1 and its paralog RC3H2 are known RNA-binding proteins that promote RNA decay 32,33 . Similar to RC3H1 , upregulation of RC3H2 in breast cancer was also correlated with poorer survival (Fig.…”
Section: Rapid-ms Specificity and New Rna–protein Interactionsmentioning
confidence: 99%
“…7a) 30,31 . RC3H1 and its paralog RC3H2 are known RNA-binding proteins that promote RNA decay 32,33 . Similar to RC3H1 , upregulation of RC3H2 in breast cancer was also correlated with poorer survival (Fig.…”
Section: Rapid-ms Specificity and New Rna–protein Interactionsmentioning
confidence: 99%
“…The NTA is followed by a helix-turn-helix motif. Interestingly, a helix-turnhelix motif contributes to RNA binding of ROQUIN (67)(68)(69), which implicates a candidate for the RNA-interaction in HCLS1. A coiled-coil region represents the main F-actin binding site and functions synergistically with the helix-turn-helix motif (70 -72).…”
Section: Novel Rna-binding Proteins In Macrophagesmentioning
confidence: 99%
“…For instance, via genome‐wide identification of Roquin target mRNAs, Roquin has been demonstrated to bind to CDEs, which canonically form triloop stem‐loop structures . In addition to this structure, recent reports using systematic evolution of ligands by exponential enrichment (SELEX) and photoactivatable ribonucleoside‐enhanced cross‐linking and immunoprecipitation (PAR‐CLIP) methods have shown that Roquin‐1 also recognises noncanonical hexaloop structures and linear binding elements (LBEs), respectively . Thus, our understanding of cis‐elements remains incomplete and further studies are necessary to comprehensively identify and validate potential RBP binding sites.…”
Section: Inflammation‐related Mrnas Are Regulated By a Set Of Rna Binmentioning
confidence: 99%